2022
DOI: 10.3390/ijms23020660
|View full text |Cite
|
Sign up to set email alerts
|

Differential Physio-Biochemical and Metabolic Responses of Peanut (Arachis hypogaea L.) under Multiple Abiotic Stress Conditions

Abstract: The frequency and severity of extreme climatic conditions such as drought, salinity, cold, and heat are increasing due to climate change. Moreover, in the field, plants are affected by multiple abiotic stresses simultaneously or sequentially. Thus, it is imperative to compare the effects of stress combinations on crop plants relative to individual stresses. This study investigated the differential regulation of physio-biochemical and metabolomics parameters in peanut (Arachis hypogaea L.) under individual (sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 93 publications
(104 reference statements)
2
24
0
1
Order By: Relevance
“…Different findings show the study of metabolomics under several environmental abiotic stresses, such as temperature [ 58 ], salinity and drought [ 59 ], and soil flooding [ 60 ]. In the same way, various metals and metalloids including, sulfur [ 61 ], phosphorus [ 62 ], oxidative stress [ 63 ], TM [ 64 ], and the combination of other several stress factors [ 65 ] in plants ( Table 1 ). Various environmental factors that could negatively disturb the homeostasis and growth of plants are shown below ( Figure 2 ).…”
Section: Metabolomics For Plant Stress Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different findings show the study of metabolomics under several environmental abiotic stresses, such as temperature [ 58 ], salinity and drought [ 59 ], and soil flooding [ 60 ]. In the same way, various metals and metalloids including, sulfur [ 61 ], phosphorus [ 62 ], oxidative stress [ 63 ], TM [ 64 ], and the combination of other several stress factors [ 65 ] in plants ( Table 1 ). Various environmental factors that could negatively disturb the homeostasis and growth of plants are shown below ( Figure 2 ).…”
Section: Metabolomics For Plant Stress Responsesmentioning
confidence: 99%
“…Additionally, ascorbic acids, glutamine, alpha-tocopherol, anthocyanins, and carotene shield plant tissues by foraging the intermediates of bustling oxygen produced during oxidative stress [ 70 ]. Similarly, several other smaller compounds guard plants against oxidation damage related to various constrictions [ 65 ].…”
Section: Metabolomics For Plant Stress Responsesmentioning
confidence: 99%
“…Metabolites are tightly related to plant phenotypes [ 25 ], as compounds that accumulate in plant organs and affect plant phenotypes [ 26 ]. In peanut, there have been several comprehensive studies of the metabolomics responses to stresses such as salt [ 27 ], drought [ 28 ] and cold stress [ 29 ]. However, metabolomics studies on peanut pod development have been scarcely reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…Cultivated peanut is widely known as an essential oilseed, protein-enrich food crop worldwide and retains important breeding traits during domestication (Zhuang et al, 2019;Bohra et al, 2022). Even so, peanut production is still substantially influenced by numerous biotic and abiotic factors (Agarwal et al, 2018;Gangurde et al, 2020Gangurde et al, , 2021Kumar et al, 2020;Shasidhar et al, 2020;Sinha et al, 2020;Jadhav et al, 2021;Pandey et al, 2021;Soni et al, 2021;Aravind et al, 2022;Bomireddy et al, 2022;Liu et al, 2022;Patel et al, 2022). When plants are exposed to diverse abiotic and biotic factors, APX enzyme as a primary marker can quickly eliminate unnecessary H 2 O 2 (i.e., ROS scavenging) from plant cells by adjusting several physiological and biochemical activities to safeguard cells from the noxiousness of overproduction of ROS (Das and Roychoudhury, 2014;Mittler, 2017;Hasanuzzaman et al, 2020Hasanuzzaman et al, , 2021.…”
Section: Characterization and Evolution Of Apx Gene Family In Plantsmentioning
confidence: 99%
“…Cultivated peanut/groundnut (A. hypogaea L.), an allotetraploid crop, is one of the most valuable and economic oilseed food crops globally (Agarwal et al, 2018;Bertioli et al, 2019;Chen X. et al, 2019;Zhuang et al, 2019). This crop is being widely cultivated in the tropical and subtropical regions globally; however, several abiotic and biotic factors significantly affect its growth and production, including many important agronomic traits (Agarwal et al, 2018;Gangurde et al, 2020Gangurde et al, , 2021Kumar et al, 2020;Pandey et al, 2020;Shasidhar et al, 2020;Sinha et al, 2020;Jadhav et al, 2021;Soni et al, 2021;Aravind et al, 2022;Bomireddy et al, 2022;Liu et al, 2022;Patel et al, 2022). Therefore, it is vital to identify new potential genes associated with multiple stress tolerance and trait improvement in peanut for better protein-rich food supply, particularly in Asian and African countries.…”
Section: Introductionmentioning
confidence: 99%